2015
DOI: 10.1007/s00228-015-1826-y
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics of S-ketamine and norketamine in healthy volunteers after intravenous and oral dosing

Abstract: Given that the analgesic effect of S-ketamine is due to both S-ketamine and norketamine, relatively small oral doses of S-ketamine can be assumed to be a feasible alternative to repeated intravenous dosing, for example in the setting of chronic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
73
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(85 citation statements)
references
References 36 publications
8
73
1
3
Order By: Relevance
“…A three‐compartment mammillary model (∆OFV = −598) with a central and two peripheral compartments was observed to be superior to a two‐compartmental model (∆OFV = −578). This was consistent with a recent study,31 developing a population model for S ‐ketamine and norketamine after oral and i.v. dosing.…”
Section: Resultssupporting
confidence: 93%
“…A three‐compartment mammillary model (∆OFV = −598) with a central and two peripheral compartments was observed to be superior to a two‐compartmental model (∆OFV = −578). This was consistent with a recent study,31 developing a population model for S ‐ketamine and norketamine after oral and i.v. dosing.…”
Section: Resultssupporting
confidence: 93%
“…Further, it has been suggested that ketamine's analgesic properties may be partially mediated by its active metabolite, norketamine. Norketamine has a longer half-life than ketamine itself, is yielded in higher concentrations than ketamine following biotransformation, and is proposed to significantly contribute to ketamine's analgesic effects [181][182][183]. Nonetheless, ketamine's use in clinical practice for pain is limited, despite promise in studies of chronic pain [184], as well as clinically applied and experimental pain models of OIH (Table 3), in part due to its cardiovascular and psychotropic side effects [172,185].…”
Section: Ketaminementioning
confidence: 99%
“…Compared to iv, the im route is associated with longer recovery time and www.nature.com/aps Gao M et al Acta Pharmacologica Sinica npg a higher rate of vomiting [13] . The oral bioavailability of ketamine is low [14] , but with small doses per os (po) S-ketamine can be assumed to be a feasible alternative to repeated intravenous injections, especially in the setting of chronic pain [15] . Intranasal (in) administration is also an option.…”
Section: Modes Of Administrationmentioning
confidence: 99%